2023
DOI: 10.1186/s13075-023-03045-3
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with discontinuation of biologics in patients with inflammatory arthritis in remission: data from the BIOBADASER registry

Abstract: Background The objectives of this study were to assess the discontinuation of biologic therapy in patients who achieve remission and identify predictors of discontinuation of biologics in patients with inflammatory arthritis in remission. Methods An observational retrospective study from the BIOBADASER registry comprising adult patients diagnosed with rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) and receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition, even among those patients who achieve clinical remission, many quickly relapse following the withdrawal of treatment 307–310. A recent study311 has looked into the real-world evidence using data from a registry of people living with inflammatory joint diseases (RA, ankylosing spondylitis or psoriatic arthritis) and treated with bDMARDs. Only 1.7% of patients with RA, 2.4% of patients with ankylosing spondylitis and 3.9% of patients with psoriatic arthritis were able to stop the bDMARD therapy reaching sustained remission.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…In addition, even among those patients who achieve clinical remission, many quickly relapse following the withdrawal of treatment 307–310. A recent study311 has looked into the real-world evidence using data from a registry of people living with inflammatory joint diseases (RA, ankylosing spondylitis or psoriatic arthritis) and treated with bDMARDs. Only 1.7% of patients with RA, 2.4% of patients with ankylosing spondylitis and 3.9% of patients with psoriatic arthritis were able to stop the bDMARD therapy reaching sustained remission.…”
Section: Implications For Treatmentmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error found in the abstract section wherein the word “shorter” should be replaced by “longer”. The correct sentence should reads:…”
mentioning
confidence: 99%